2002
DOI: 10.1021/jo016212b
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Suzuki Coupling−Norbornadiene Insertion Reactions. A Convenient Route to 5,6-Diarylnorbornene Compounds

Abstract: This paper presents optimization studies on a palladium-catalyzed tandem norbornadiene insertion-Suzuki coupling reaction, which provides a one-pot procedure for the formation of diarylnorbornene derivatives. This procedure allows for the synthesis of these compounds from readily available aryl halides, arylboronic acids, and substituted norbornadienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Later in 1998, Kang and coworkers also demonstrated that Pd‐catalysts could catalyze the selective difunctionalization of one olefin in norbornadiene with ArN 2 BF 4 or Ph 2 IBF 4 and a variety of nucleophiles such as alkynes, PhSnBu 3 , NaBPh 4 and PhB(OH) 2 (Scheme ) . A similar reaction of selective difunctionalization of one olefin in norbornadiene was also reported by Goodson and coworkers by using aryl halides and ArB(OH) 2 as carbon sources in the presence of Pd(OAc) 2 as a catalyst (Scheme ) …”
Section: Intermolecular Dicarbofunctionalization Of Olefinsmentioning
confidence: 99%
“…Later in 1998, Kang and coworkers also demonstrated that Pd‐catalysts could catalyze the selective difunctionalization of one olefin in norbornadiene with ArN 2 BF 4 or Ph 2 IBF 4 and a variety of nucleophiles such as alkynes, PhSnBu 3 , NaBPh 4 and PhB(OH) 2 (Scheme ) . A similar reaction of selective difunctionalization of one olefin in norbornadiene was also reported by Goodson and coworkers by using aryl halides and ArB(OH) 2 as carbon sources in the presence of Pd(OAc) 2 as a catalyst (Scheme ) …”
Section: Intermolecular Dicarbofunctionalization Of Olefinsmentioning
confidence: 99%
“…[59] Therefore,norbornenes with definite configuration produced by stereoselective reaction are necessary for controlling alignment of the substituents (that is,d onor and acceptor). Herein, at andem Suzuki coupling-norbornadiene insertion reaction of aryl iodide and arylboronic ester in presence of norbornadiene [60] is used for preparation of disubstituted monomers because they can selectively afford cis, exo-isomers in which donor and acceptor are aligned in the same side of norbornene skeleton. By using Pd(OAc) 2 /PPh 3 as catalyst, three disubstituted norbornene monomers are obtained.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…In line with this, a great deal of interest has been devoted to norbornene 1 and its analogues [6][7]. Syncarbopalladation of these alkenes with aryl or vinyl halides may be terminated by stereoselective trapping with nucleophiles such as alkenyl stannanes 2 (Stille coupling) [7], terminal acetylenes 3 (Cassar/Sonogashira coupling) [8,9], tetraaryl borates 4 [10] and boronic acids 5 (Suzuki coupling) [11,12], or cyanide ion [13] (Scheme 8.1). Scheme 8.2 illustrates the potential applications of such vicinal difunctionalization reactions to the construction of leucotriene model compounds 6 [14].…”
Section: Carbopalladation Of Norbornene and Its Analoguesmentioning
confidence: 99%